Re-Interpretasi Formasi Kerek Di Daerah Klantung, Kendal, Berdasarkan Data Stratigrafi dan Foraminifera - Putra, Purna Sulastya; Praptisih, Praptisih (Jurnal Geologi dan Sumberdaya Mineral, 2017)
Rock unit crops out surrounding the Cipluk oil field is part of the Kerek Formation according to the regional geological map, however, the stratigraphy, depositional environment and relative age of the rock unit is not clearly recognised. Detailed stratigraphic and micropaleontological studies have been done in the rock unit surrounding the Cipluk of  oil field. The results show that the rock outcrops in the study area are composed by a repetition of marl intercalated by sandstones,identified as turbiditic facies part of a channel portion of supra fan lobe to outer fan that deposited in an upper bathyal. Based on planktonic foraminifera content, the relative age of rockunit is Pliocene to Late Pleistocene. According to the litological characteristics and relative age data, the rock unit in studied area seems to be not part of the Kerek Formation, but it belongs to part of the Kalibeng Formation. The result of this study is very important for updating the surface geological data in which will be very useful to understand the new petroleum system in this area. Keywords: Kerek Formation, Cipluk oil field, turbidite, Kalibeng Formation